Peran Job Satisfaction dalam mediasi hubungan Strategic Flexibility dan Strategic Innovation dengan Employee Performance - Purnama, Chamdan; Rahmah , Mirhamida; Fatmah, Dinda; Hasani , Syaiful; Rahmah, Yusriyah; Rahmah, Zakiyah Zulfa; Mulyono, Sugeng; Anam, Chairul (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research aim: This study examines the relationships between strategic flexibility, behaviour innovation, Employee engagement, Job satisfaction, and employee Performance within SMES in the clothing sector in East Java. It also provides empirical evidence of causal interactions among these variables. Method: An explanatory approach was employed with a sample of 160 employees from SMES in Bangkalan, Sidoarjo, Tulungagung, and Mojokerto, selected via cluster sampling. Data were collected using a Likert-scale questionnaire and analysed using PLS-SEM with Smartpls 4. Research Finding: The findings show that strategic flexibility positively and significantly influences employee Performance and Job satisfaction. Behaviour innovation negatively impacts employee Performance but positively affects Job satisfaction. Employee engagement positively influences employee Performance but is not significant for Job satisfaction. Job satisfaction partially mediates the relationship between strategic flexibility and employee Performance and fully mediates the relationship between behaviour innovation and employee Performance. Theoretical contribution: This study challenges existing assumptions about the link between Employee engagement and Job satisfaction, expanding understanding in the context of SMES. Practical implication: The findings suggest that SME managers should enhance strategic flexibility and focus on Job satisfaction to improve employee Performance while carefully managing behaviour innovation. Research Limitations: This study has several limitations. First, the study was only conducted on MSMES in the clothing sector in East Java. Second, the data collection method used a Likert-scale questionnaire. Third, the quantitative approach with PLS-SEM provides an understanding of causal relationships but does not explore other factors that may play a role.